2022
DOI: 10.1186/s12888-022-04186-6
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and academic performance mediates the relationship between fear of missing out and smartphone addiction among Iranian university students

Abstract: Background Fear of missing out (FoMO) can increase loneliness and smartphone addiction and decrease academic performance in university students. Most studies investigated the relationship between FoMO and smartphone addiction in developed countries, and no studies were found to examine this association in Iran. The mediating role of loneliness and academic performance in the relationship between FoMO and smartphone addiction is unclear. This study investigated the relationship between FoMO and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 58 publications
2
29
0
1
Order By: Relevance
“…Therefore, individuals more satisfied with their relationships are less likely to perceive others as having more rewarding experiences and are less likely to be jealous of their friends (Yin et al, 2021 ), thus experiencing less trait-FoMO. Consistent with previous research, trait-FoMO is positively associated with loneliness (Fumagalli et al, 2021 ; Alinejad et al, 2022 ). Trait-FoMO results from the absence of social needs (Przybylski et al, 2013 ; Wegmann et al, 2017 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, individuals more satisfied with their relationships are less likely to perceive others as having more rewarding experiences and are less likely to be jealous of their friends (Yin et al, 2021 ), thus experiencing less trait-FoMO. Consistent with previous research, trait-FoMO is positively associated with loneliness (Fumagalli et al, 2021 ; Alinejad et al, 2022 ). Trait-FoMO results from the absence of social needs (Przybylski et al, 2013 ; Wegmann et al, 2017 ).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, trait-FoMO may lead to an increase in loneliness. Prior cross-sectional research has demonstrated a positive association between the trait-FoMO and loneliness (Fumagalli et al, 2021;Alinejad et al, 2022). Moreover, studies with Experience Sampling Method (ESM) have shown that daily trait-FoMO increases individuals' negative affect, such as anxiety, depression, and stress, the next day and decreases positive affect (Milyavskaya et al, 2018;Elhai et al, 2020).…”
Section: Negative E Ects: the Mediating Role Of State-fomomentioning
confidence: 99%
“…Smartphones have become essential for college students in their daily lives and studies. Because of its functional characteristics (e.g., collectivity of functions, personalization and customization of content, accessibility, and convenience), smartphones become a tool for college students with school maladjustment to obtain alternative satisfaction and compensation, which easily leads to smartphone addiction ( Aker et al, 2017 ; Boumosleh and Jaalouk, 2017 ; Kim et al, 2017 ; Bian et al, 2018 ; Alinejad et al, 2022 ). Therefore, based on empirical and theoretical evidence, the above relationship between meaning in life, school adjustment, and smartphone addiction could be well comprehended.…”
Section: Discussionmentioning
confidence: 99%
“…Some empirical studies support the notion of self-determination theory. For example, with regard to the relationship between emotional adjustment and college students’ smartphone addiction, some studies have reported that depression ( Aker et al, 2017 ; Boumosleh and Jaalouk, 2017 ; Kim et al, 2017 ), anxiety ( Aker et al, 2017 ; Boumosleh and Jaalouk, 2017 ; Kim et al, 2017 ), and loneliness ( Kim et al, 2017 ; Alinejad et al, 2022 ) are positively related to college students’ smartphone addiction. Moreover, one empirical research confirmed that alexithymia not only directly affected college students’ smartphone addiction, but also indirectly affected their smartphone addiction through depression, anxiety, and stress ( Gao et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In line with a growing number of studies we observed a positive association between higher levels of FOMO and more problematic smartphone and social media usage. On the one hand, FOMO has for instance been associated with development of problematic usage of a number of internet applications, including problematic internet usage (Röttinger et al, 2021) and smartphone addiction (Alinejad, Parizad, Yarmohammadi, & Radfar, 2022). However, on the other hand, an increasing number of studies underscore the role of social and self-related cognitions in this association such that the association between FOMO and smartphone addiction is mediated by loneliness (Alinejad et al, 2022) while FOMO mediates the association between parental support, self-construal, self-concept clarity or interpersonal sensitivity with problematic smartphone use (Kim, 2022; Lin et al, 2021; Servidio, Sinatra, Griffiths, & Monacis, 2021).…”
Section: Discussionmentioning
confidence: 99%